Alpha diversity of marine mammals of the Mexican South Pacific - Francisco Villegas-Zurita; Fátima Castillejos-Moguel; Francisco Benítez-Villalobos; Jorge Urbán-Ramírez (Revista Mexicana de Biodiversidad)
Knowledge of the alpha diversity contributes to the determination of conservation priorities by identifying regions with high species richness and/or a large number of endemic, rare, or endangered species. The present study focused on the evaluation of species richness and composition of the marine mammal community off the coast of Oaxaca. A total of 293 surveys were carried out between December 2011 and April 2015. Additionaly, observation and stranding records found in the literature and zoological collections (corresponding to the period 2008-2014) were revised to estimate alpha diversity. The results allowed us to conclude that the current richness of marine mammals for the state, comprises 21 species distributed in 2 orders, 3 suborders, 5 families, and 17 genera. This represents a 75% increase in the known richness prior to this study. All species of marine mammals are found in some risk category according to the NOM-059-Semarnat-2010 (Mexico), IUCN, and CITES. Our results highlight the importance of the Oaxaca region in the Mexican South Pacific as a priority area for conservation, because of its high degree of richness, considerable diversity in species composition, and the concentration of vulnerable or endangered marine mammals.